2021
DOI: 10.1088/1757-899x/1013/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Laser Surface Texturing of Eutectic Al-Si Alloy

Abstract: Relative movement between piston and cylinder of an IC engine contributes to more than 60% of the friction experienced by the engine - in turn contributing to the wear of the piston and hence loss in its operational performance and efficiency. It is pertinent to explore technological solutions to overcome this situation. Texturing of surfaces appears to be an useful technique to enhance the tribological performance of the piston and cylinder assembly and information about the same are available in published li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…If the counter-surface contact width was bigger than the feature dimension, it was shown that textured features might reduce the average coefficient of friction by as much as 37% through a lubricant reservoir mechanism. A typical piston material, such as a eutectic Al-Si alloy, was laser surface texturized using a high power CO2-CW laser, according to Nandakumar et al [27]. The tests were performed in two ways: first, to determine the ideal laser processing parameters to produce surfaces that can hold oil; and second, to conduct a typical study of the test material's surface quality after laser texturing.…”
Section: Introductionmentioning
confidence: 99%
“…If the counter-surface contact width was bigger than the feature dimension, it was shown that textured features might reduce the average coefficient of friction by as much as 37% through a lubricant reservoir mechanism. A typical piston material, such as a eutectic Al-Si alloy, was laser surface texturized using a high power CO2-CW laser, according to Nandakumar et al [27]. The tests were performed in two ways: first, to determine the ideal laser processing parameters to produce surfaces that can hold oil; and second, to conduct a typical study of the test material's surface quality after laser texturing.…”
Section: Introductionmentioning
confidence: 99%